Relaxation caused by one phonon decay into three in superfluid helium - Adamenko, I.N.; Kitsenko, Yu.A.; Nemchenko, K.E.; Slipko, V.A.; Wyatt, A.F.G. (Вопросы атомной науки и техники, 2007)
The analytical relation for the rate of one phonon decay into three is obtained. Starting from the relation obtained, the rate of spontaneous decay in the first order of perturbation theory is found. It is shown, that processes of one phonon decay into three provide a fast establishment of equilibrium in anisotropic and isotropic phonon systems. It allows us to relate the momentum region in which processes of one phonon decay into three are permitted to subsystem of low-energy phonons. Отримано аналітичний вираз для частоти процесів розпаду одного фонона на три. Виходячи з отриманого виразу, знайдено частоту самовільного розпаду в першому порядку теорії збурень. Показано, що процеси розпаду одного фонона на три забезпечують швидке встановлення рівноваги в анізотропних і ізотропних фононних системах. Це дозволяє область, у якій дозволені процеси розпаду одного фонона на три, віднести до підсистеми низькоенергійних фононів. Получено аналитическое выражение для частоты процессов распада одного фонона на три. Исходя из полученного выражения, найдена частота самопроизвольного распада в первом порядке теории возмущений. Показано, что процессы распада одного фонона на три обеспечивают быстрое установление равновесия в анизотропных и изотропных фононных системах. Это позволяет область, в которой разрешены процессы распада одного фонона на три, отнести к подсистеме низкоэнергетических фононов.